2005
DOI: 10.1080/j003v19n01_14
|View full text |Cite
|
Sign up to set email alerts
|

Education and Practice Collaborations: A Pilot Case Study Between a University Faculty and County Jail Practitioners

Abstract: SUMMARY The purpose of this case study is to present a partnership between faculty and practitioners that initiated a systematic evaluation data collection approach to support program development and study practice in a newly developing occupational therapy program. The Department of Occupational Therapy at Duquesne University collaborated with Goodwill Industries of Pittsburgh to introduce occupational therapy as part of a grant-supported community re-integration program at the Allegheny County Jail. In devel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 5 publications
0
7
0
Order By: Relevance
“…From a therapeutic perspective, occupational adaptation was applied and defined as the process of adapting the self and the environment to provide holistic care or intervention (Dale et al, 2002). Crist et al (2005) reinforced the environment as a significant influence on the occupational adaptation process. Using perspectives from individuals who have experienced various life-altering situations, Spencer, Davidson, and White (1996) defined occupational adaptation as knowing how to respond to different challenges based on familiarity of the environment.…”
Section: Thematic Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…From a therapeutic perspective, occupational adaptation was applied and defined as the process of adapting the self and the environment to provide holistic care or intervention (Dale et al, 2002). Crist et al (2005) reinforced the environment as a significant influence on the occupational adaptation process. Using perspectives from individuals who have experienced various life-altering situations, Spencer, Davidson, and White (1996) defined occupational adaptation as knowing how to respond to different challenges based on familiarity of the environment.…”
Section: Thematic Analysismentioning
confidence: 99%
“…Occupational adaptation was defined in the literature as an ongoing, non-linear process to achieve a desired sense of self (Lexell, Iwarsson, & Lund, 2011); a manner of developing a sense of competence, self-efficacy, and identity in occupational participation (Johansson & Isaksson, 2011;Yazdani, 2011;Crist et al, 2005;Firfirey & Hess-April, 2014); and a manner of reframing identity, competence, the environment, and the fit between all three (Klinger, 2005;Mallinson, Mahaffey, & Kielhofner, 1998). In addition, Luck and Beagan (2015) asserted the reciprocal process between occupational adaptation and identity.…”
Section: Thematic Analysismentioning
confidence: 99%
“…Chui (in press) reported that Canadian practitioners she surveyed utilized a very wide variety of assessment tools. Within the international criminal justice literature, studies can be found that employed a similarly wide array of assessment tools to measure outcomes including the MOHO Screening Tool (Fitzgerald, ), the Occupational Self Assessment (Crist et al, ), the Assessment of Motor and Process Skills (Fisher, ), the Assessment of Communication and Interaction Skills (Fitzgerald et al, ), the Occupational Questionnaire (Stewart and Craik, ), the Occupational Therapy Task Observation Scale (Smith et al, ) and the Allen Cognitive Level Screen (Lindstedt et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Examples of program evaluation in the literature include Crist et al . () who evaluated the effectiveness of collaboration between an academic department and Goodwill Industries. The program included educational and other interventions to: “… (1) change habit patterns; (2) consider work behaviors and employment options; and (3) develop inmate‐practitioner relationships pre‐release in order to sustain post‐release support for engagement in a new, productive lifestyle upon release” (p. 198).…”
Section: Literature Reviewmentioning
confidence: 99%